The Use of International Standards of Accounting Education in Developing Professional Skills in Accounting Education Faculty of Economics and Commerce, Al-Merqeb University (Journal of human and social sciences, 2022)
specific contact with the labor market. But what we can see in the Libyan case even university education in general or accounting education in specific, there is no census between the output of the education and the needs of labor market. Therefore, this study aimed to demonstrate the important role of the accounting education in Elmergib University for developing professional skills of alumni students according to the third principle of the accounting education principles, which issued frothe international union of accountant, whereas the last one specified the professional skills in main five groups وwhich are Intellectual skills, Technical and practical skills, personal skills, connection skills, and communication skills. This study used questionnaire survey to collect information from research population (Lectures of Accounting Department in Economic and Commerce Faculty of El-mergib University) where, their numbers is 29, and the real respondents were around 82% , and the software program of SPSS was used to analyze the data. The results showed that the accounting education has played an important role to develop Intellectual skills, Technical and practical skills and personal skills, whereas, it manages to develop connection skills and communication skills. This study recommended developing the accounting education by teaching technique or courses, which can develop the personal skills to the alumni and can give capacity for self-learning and self-management, as well as the capacity of linking the academic case with labor market
Keywords: : Accounting Education, Elmergib University; Libya